Managing publicly - Mintzberg, Henry (Canada, 2000)
The public sector's management been so high. As the performance of the state apparatus is monitored and held to a very high standard, the role of public sector managers has become more complicated. They are asked to manage in the style of the private sector while respecting the values of the traditional public sector and their performance is evaluated daily by politicians, the media and the public.
Keywords: Public administration-Canada